(untitled) (AYUSHDHARA, 2015)
The proper understanding of terminology is vital for a systematic knowledge of any structure especially in context of Sharira Rachana. A term is a structured set of concepts and their designations in a specific field. The proper terminology is concerned with relationship between the concepts and also makes a fundamental pillar. The aim of present article is to compiled, critically analyze the terminology related to Artava i.e. Raja, Artava and Shonita and elaborate the fundamental concepts behind those terminologies in various classics of Ayurveda. Presence of Raja, Artava since childhood, concept of Raja, Shonita, character of Artava and difference between Artava and Shonita are mentioned as reviewed literature. About one month of time period is needed in the formation of Artava in adult female’s means to reach the Artava from its originating place to destination place or from Yakrita and Pleeha to Garbhashaya (Yoni) and this makes complete passage of Artava. Artava have Agneya Pradhana nature as source of Agneyatattva for Garbha while Anushanasheeta composition of Rakta Dhatu laid the foundation of Dhatu for body. Raja is the flowing constituent of Artava and Beeja as constituent of Artava is the source of Garbha. Both Artava and Rakta Dhatu are formed from Rasa Dhatu by Ranjanakriya. This process converts the Saumyabhava to Agneyabhava. This article can be helpful to understand the various terminologies related to the Artava.